Learning Technologies and Leadership in Learning Organizations: A Systematic Literature Review - Cicilia Emita; Bambang Wiyoso; Dilla Maidaliza; Robinson Situmorang; Muhammad Japar (Ilomata International Journal of Social Science, 2026)
This paper examines how leadership, organizational learning, and technology integration interact to foster innovation and adaptability within learning organizations in the context of digital transformation. While prior studies have largely examined these elements in isolation, there remains limited synthesis of how leadership, learning processes, and digital technologies jointly operate across organizational contexts. This review is novel in that it systematically integrates leadership styles, organizational learning processes, and digital transformation within a single analytical framework and classifies existing empirical studies according to direct, moderation, and mediation models. Using a systematic literature review guided by PRISMA, the study synthesises 23 peer-reviewed empirical articles published between 2015 and 2025 across education, healthcare, public, and private sector organizations. The findings show that leadership influences organizational learning and performance through both direct and indirect pathways, with effects shaped by contextual conditions such as organizational flexibility and sectoral characteristics. Mediation mechanisms, particularly employee productivity and knowledge sharing, are central in translating leadership practices and technology adoption into improved organizational outcomes. Moderation effects further indicate that leadership effectiveness varies according to organizational readiness and environmental complexity. The review highlights that context-sensitive leadership and strategically aligned digital learning initiatives are critical for sustainable organizational development. It concludes by recommending that future research and policy prioritize integrated and adaptive approaches to leadership development and digital learning, offering a coherent roadmap for scholars and practitioners seeking to build resilient and innovative learning organizations.